IMPLEMENTASI PENILAIAN SIKAP SPIRITUAL DALAM PEMBELAJARAN TEMATIK DI KELAS IV SEKOLAH DASAR ISLAM AL-AZHAR 21 - Rini Januarti; Asrori Asrori; Yulis Jamiah (Universitas Tanjungpura, 2017)
Abstract:This research aimed to describe the implementation of spiritual attitudes assessment in thematic learning. This research was a case study of qualitative approach. Data collected by observation, interview, and documentation. The subject of this research were teacher, students, and headmaster. The results indicate that: (1) the planning of spiritual attitude assessment through determining attitude to be observed, attitude indicators, and assessment instrument; (2) the realization of spiritual attitude assessment through observing students behavior at learning process and following up the observation; (3) the analysis of spiritual attitude assessment done by making attitude recapitulation every three to six months using microsoft excel program; (4) the constraints of spiritual attitude assessment is that assessment instrument was not in Kurikulum 2013 standard, the assessment instrument required more time to use so carefulness of observation required to observe the students; and (5) the strategy to resolve the constraints is by cooperating in teacher working group and discussing with other teacher or deputy of curriculum. Keywords: assessment, spiritual attitude, thematic learning